Effects of resistance training and detraining on muscle strength and blood lipid profiles in postmenopausal women. Issue 5 (1st October 2002) - Elliott, K J; Sale, C; Cable, N T
Abstract : Objectives: To study the effects of eight weeks of supervised, low intensity resistance training (80% of 10 repetition maximum (10RM)) and eight weeks of detraining on muscle strength and blood lipid profiles in healthy, sedentary postmenopausal women. Subjects: Fifteen postmenopausal women, aged 49–62 years, took part in the study. Subjects were assigned to either a control (n = 7) or training (n = 8) group. The training regimen consisted of three sets of eight repetitions of leg press, bench press, knee extension, knee flexion, and lat pull-down, three days a week at 80% of 10RM. Dynamic leg strength, 10RM, and blood lipid profiles (total cholesterol (TC), low and high density lipoprotein cholesterol (LDL-C, HDL-C), triglycerides, and very low density lipoprotein cholesterol (VLDL-C)) were measured at baseline, after eight weeks of training, and after a further eight weeks of detraining. Results: Eight weeks of resistance training produced significant increases in knee extension ( F 1, 13 = 12.60; p<0.01), bench press ( F 1, 13 = 13.79; p<0.01), leg press ( F 1, 13 = 15.65; p<0.01), and lat pull-down ( F 1, 13 = 16.60; p<0.005) 10RM strength tests. Although 10RM strength decreased after eight weeks of detraining, the results remained significantly elevated from baseline measures. Eight weeks of training did not result in any significant alterations in blood lipid profiles, body composition, or dynamic isokinetic leg strength. There were no significant differences in any of the variables investigated over the 16 week period in the control group. Conclusions: These data suggest that a short, low intensity resistance training programme produces substantial improvements in muscle strength. Training of this intensity and duration was not sufficient to produce significant alterations in blood lipid concentrations.